Pengembangan Media Pembelajaran Interaktif “Biolens Fungi” Berbantuan Website pada Mata Pelajaran Biologi Kelas X SMA - Fajar, Muhammad Ardi; Rayendra; Zen, Zelhendri; Darmansyah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The low scientific literacy and students' difficulties in visualizing the microscopic and abstract structure of fungi indicate the need for interactive digital learning media that supports visual understanding. This study aims to develop a website-based interactive media "BioLens Fungi" and test its validity, practicality, and effectiveness in learning Fungi material for grade X of high school. This study is a research and development (R&D) using a 4D model. The research subjects consisted of 31 students of SMAN 1 Pasaman, while the validity of the media was assessed by material experts and media experts. Data were analyzed descriptively quantitatively through the percentage of validity and practicality as well as N-Gain analysis and statistical tests on the results of the pretest and posttest. The media was developed using Canva and 3D Assemblr objects. The results showed material validity of 95.00%, media validity of 88.39%, and practicality of 97.74%, all of which are in the very valid and very practical categories. Learning outcomes increased from an average of 34.19 to 91.77 with an N-Gain of 0.88 in the high category. Thus, BioLens Fungi meets the feasibility and practicality criteria and demonstrates effectiveness in supporting students' understanding of Fungi material through digital-based interactive visualization.